Personal digital Mutawwif: A multi-modal mobile Hajj assistance using the location based services - Al-Aidaroos, Ahmed Sheikh Abdullah; Abdul Mutalib, Ariffin (Penerbit UTM Press, 2015)
Many efforts have been initiated and many techniques and approaches have been developed to facilitate the difficulties faced by pilgrims. However, those studies focus on acquiring initial perspective and background knowledge about Hajj before going to Makkah.In conjunction to that, this study utilizes A-GPS in mobile phone to assist the pilgrims during Hajj.The main aim of this paper is to discuss about the development of a multi-modal mobile application called the Personal Digital Mutawwif (PDM), using location based services to assist pilgrims while performing all the rituals of Hajj.Android platform has been chosen due to the dramatic increased in the Android mobile phone users worldwide. PDM displays the Arabic text, the translation in Malay and also the Arabic audio files of the dua and zikr, which has been gathered, compiled, and verified before the development using Java 2 Platform, Micro Edition (J2ME). The application has been proven to be useful in helping the pilgrims to easily and conveniently recite the dua and zikr towards achieving Hajj Mabrur.